Peramalan Tren Produk Pakaian Menggunakan Metode SARIMA pada Data Google Trends - Muhammad Hilmi Syarif; Nana Mulyana Maghfur; Budi Arif Dermawan (Peneliti.net, 2023)
The development of the digital era is very rapid at this time there are so many technologies that are present in human life, one of which is e-commerce. Today's society is very dependent on what is called e-commerce, there are lots of transactions made every year from 2017 there are around 8,657 USD until 2021 which continues to increase to 53,808 USD. This is more or less influenced by advertisements scattered in cyberspace. In 2020, the 1st rank of the highest number of transactions is held by clothing products, so sellers from e-commerce need to be assisted with a recommendation system that displays the best time to display their advertisements. The process uses the time-series forecasting method using the SARIMA algorithm. This algorithm takes the trend of the season from the previous data, so it is very suitable for the cases mentioned earlier. The data retrieval processes up to deployment to the web system uses the CRISP-DM research method. The results of this study have a very good evaluation value, namely with an R2 of 0.36993 so that the model is good to use and in its implementation is a web system that takes the category and how long it will be predicted.